PRINCIPAL COMPONENT ANALYSIS MODEL TO REDUCE COMPLIANCE FACTORS OF MEDICAL NUTRITION THERAPY IN HYPERTENSION PATIENTS - Dian Isti Angraini; Sofyan Musyabiq Wijaya; Novita Carolia; Efriyan Imantika (Majalah Kedokteran Sriwijaya, 2025)
The prevalence of hypertension is increasing, both at all ages and everywhere, and is one of the contributors to death due to complications. Morbidity and mortality due to hypertension can be prevented by implementing appropriate treatment, one of which is medical nutrition therapy. This research aims to analyze factors associated with compliance with medical nutrition therapy in hypertensive patients using principal component analysis. This study is an observational analytic using a cross sectional design. The research started from August to October 2023. The samples for this study were 100 hypertensive patients in the Kedaton Health Center work area and were taken using a multistage random sampling technique that met the inclusion and exclusion criteria. The independent variables are knowledge, education, income, attitude, motivation, self-efficacy, family support, food availability in the household, psychological conditions, and support from health workers; and the dependent variable is compliance with medical nutrition therapy. Data were analyzed using principal component analysis. The results of the study showed that based on principal component analysis, 3 categories of factors were found that played a role in the compliance of medical nutrition therapy in hypertensive patients, namely factor 1 socioeconomic, efficacy, and psychology (education, knowledge, income, efficacy, psychology), factor 2 personal and nutrition (attitude, motivation, food availability), and factor 3 reinforcing (family support, health worker support).